PENGARUH SALES PROMOTION DAN E-WOM MELALUI POSITIVE EMOTION TERHADAP IMPULSIVE BUYING PADA MAHASISWA - Rastika Erning Bidari; Salman Alfarisy Totalia (STKIP Persada Khatulistiwa Sintang, 2026)
This study aims to determine the effect of sales promotion and E-WOM through positive emotion on impulsive buying among students. This study aims to determine the effect of sales promotion and E-WOM through positive emotion on impulsive buying among university students. This study uses a quantitative approach. Data were collected through Google Forms with a sample of 117 economics students at UNS. The sampling technique used probability sampling with the proportionate stratified random sampling method. Data analysis was conducted using SEM-PLS and processed through SmartPLS version 4.0. The results of the study indicate that (1) sales promotion has a positive and significant effect on impulsive buying (2) electronic word of mouth has a negative and significant effect on impulsive buying (3) sales promotion has a positive and significant effect on positive emotion (4) electronic word of mouth has a positive and significant effect on positive emotion (5) positive emotion has a positive and significant effect on impulsive buying (6) sales promotion through positive emotion has a positive and significant effect on impulsive buying (7) electronic word of mouth through positive emotion has a positive and significant effect on impulsive buying. Based on the results of this study, students need to improve their self-control, financial management, and emotional management, as well as be more selective about promotions and recommendations from others in order to reduce impulsive buying. The limitations of this study are that the variables and subjects are still limited, focusing only on the Shopee marketplace and online impulsive buying behavior.